Monitoring and numerical modeling of a road in landslide terrain = Monitoring i modelowanie numeryczne drogi kołowej w terenie osuwiskowym - Kogut, Janusz; Pilecka, Elżbieta; Szwarkowski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Due to the significant role and noticeable development of transportation routes running from the north to the south of central Europe, several problems related to the construction and functioning of roads in the Carpathian foothills have been revealed. Recent climate change causes areas, where transport routes are particularly exposed to hazards, to succumb to technical exploitation and degradation.
Keywords: landslides; monitoring; stability; road; numerical modeling; osuwisko; stateczność; droga; modelowanie